Seroepidemiological and phylogenetic characterization of neurotropic enteroviruses in Ireland, 2005‐2014. Issue 9 (6th June 2017) - Guerra, Jorge Abboud; Waters, Allison; Kelly, Alison; Morley, Ursula; O'Reilly, Paul; O'Kelly, Edwin; Dean, Jonathan; Cunney, Robert; O'Lorcain, Piaras; Cotter, Suzanne; Connell, Jeff; O'Gorman, Joanne; et al.
Abstract : Enteroviruses (EVs) are associated with a broad spectrum of clinical presentation, including aseptic meningitis (AM), encephalitis, hand, foot and mouth disease, acute flaccid paralysis, and acute flaccid myelitis. Epidemics occur sporadically and are associated with increased cases of AM in children. The present study describes the seroepidemiological analysis of circulating EVs in Ireland from 2005 to 2014 and phylogenetic characterization of echovirus 30 (E‐30), enterovirus A71 (EV‐A71), and enterovirus D68 (EV‐D68). EV VP1 genotyping was applied to viral isolates and clinical samples, including cerebrospinal fluid (CSF), and those isolates that remained untypeable by neutralising anti‐sera. An increase in AM cases from 2010 to 2014 was associated with an E‐30 genogroup variant VII and sequences clustered phylogenetically with those detected in AM outbreaks in France and Italy. EV‐D68 viral RNA was not detected in CSF samples and no neurological involvement was reported. Three EV‐A71 positive CSF samples were identified in patients presenting with AM. A phylogenetic analysis of respiratory‐associated EV‐D68 and EV‐A71 cases in circulation was performed to determine baseline epidemiological data. EV‐D68 segregated with clades B and B(1) and EV‐A71 clustered as subgenogroup C2. The EV VP1 genotyping method was more sensitive than neutralising anti‐sera methods by virus culture and importantly demonstrated concordance between EV genotypes in faecal and CSF samples which should facilitate EV screening by less invasive sampling approaches in AM presentations.